The politics of promoting social protection in Zambia - Kate Pruce; Sam Hickey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper examines the rise of the social protection agenda in Zambia, and demonstrates that this has two alternative drivers: shifting dynamics within Zambia's political settlement and the promotional efforts of a transnational policy coalition. We compare the cases of social cash transfers and social health insurance to investigate how the interplay of these drivers has shaped the uneven commitment to the respective policies. Social protection has yet to displace existing interests, ideas, and rent-allocation practices. However, cash transfers are gaining localized support. What matters now is the way in which such transfers become integrated within Zambia's distributional regime.
Keywords: H51; H53; I13; I38; 330; cash transfers; ideas; political settlements; social health insurance; social protection; Zambia